Implementation of The PBL Learning Model in Controversial Historical G30S Materials - 'Aini, Syavila Nur (JURNAL HISTORICA, 2024)
This research aims to analyze the effectiveness of using the problem-based learning model in controversial material in Indonesian history, in particular the events that occurred in 1965, which involved many parties, especially the PKI and the army. The event that occurred in 1965 is known as the G30S incident. Even though this incident occurred 58 years ago, to this day, the G30S incident is still controversial in Indonesian society. The controversial position of the G30S incident is regarding who was the mastermind behind the bloody incident that killed Army generals and one officer in a tragic way. Within the scope of history education, material discussing the G30S incident is also still being debated. Therefore, appropriate learning strategies are needed in delivering the material, for example, using the problem-based learning model to improve students' critical thinking skills in studying the G30S incident.